(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents the theoretical-methodological basis of geographical research of enclave regions, which are the result of a unique border between countries. Taking into account that enclave regions are a geographical category, the results of the research conducted by foreign and local researchers in this direction were analyzed. Based on the conclusions obtained from the analysis of scientific literature, the processes related to the enclave regions are divided into vector relations and their methodological aspects are highlighted.